THE EFFECT OF TED TALKS VIDEO TOWARDS STUDENTS’ SPEAKING ABILITY AT ENGLISH STUDY PROGRAM OF FKIP UIR: (Pengaruh Video TED TALKS Terhadap Kemampuan Berbicara Mahasiswa Pendidikan Bahasa Inggris FKIP UIR) - Betty Sailun; Andi Idayani (UIR Press, 2018)
In University level, speaking is one of important skill that used be mastered by the English Students, because it is necessary for them to improve their ability to communicate orally by presenting their ideas in real life. Hence, TED is a series of informative, educational, inspiring and sometimes jaw-dropping talks that present ‘Ideas Worth Spreading’. There is an emphasis on informing, educating and opening people’s eyes to new ideas, making them perfect for the classroom. Therefore, the students will have the opportunity to develop their spoken language competence. In relation to this, the researcher was interested in conducting a study which was focused on the effect of TED Talks Video toward students’ speaking ability at the third semester of English Study Program FKIP UIR. The researchers used experimental research and also used speaking test for pre-test and post-test in both of experiment class and control class as a collecting data of research. Based on the result, it can be seen that the value of t-obs was higher than that of t-table (3,217>2.056). In addition, the value of probability significance (2-tailed) column shows 0.002<0.05. Based on the analysis, those two criteria of rejection are fulfilled. Therefore, it can be concluded that the null hypothesis was rejected and alternative hyphotesis was accepted. Consequently, it could be seen that there was a significant mean difference between the experimental and the control groups. In summary, there was a significant effect of TED Talks video toward students’ speaking ability at English Study Program FKIP UIR